A Perbandingan Efektifitas Terapi Yasmin Dengan Rileksasi Guide Imaginary dalam Meningkatkan Kualitas Tidur pada Lansia di Panti Harapan Kita Ogan Ilir - Jaji Jaji; Jum Natosba; Sukmah Fitriani; Khoirul Latifin (Jurnal Ners, 2026)
Sleep is one of the basic biological needs of humans that is very important for maintaining physiological and psychological functions. Good quality sleep supports overall health, including immunity, brain function, and emotional stability. Sleep disorders in the elderly are influenced by various factors such as physiological changes, chronic medical conditions, and psychosocial factors. Non-pharmacological approaches are a safer and recommended alternative. Two complementary therapies that are increasingly being used are Yasmin flower aromatherapy and guided imagery relaxation therapy. The purpose of this study is to determine which therapy is more effective between Yasmin flower aromatherapy and guided imagery in reducing Pittsburgh Sleep Quality Index (PSQI) scores in the elderly. This study is a quantitative study with a quasi-experimental design using a two-group pretest-posttest model without a control group. The aim is to compare the effectiveness of jasmine aromatherapy and guided imagery relaxation on improving sleep quality in the elderly. The sample was selected using purposive sampling. The research instrument, the Indonesian version of the PSQI, was used to measure the respondents' sleep quality and had 7 components with a score range of 0–21. A score > 5 indicated sleep disturbance. The results showed that both interventions, Yasmin aromatherapy and guided imagery therapy, obtained a p-value of 0.001 (p < 0.05) using a paired t-test, indicating a significant effect on improving the sleep quality of the elderly. However, the results of the independent t-test between the two groups showed that the Yasmin aromatherapy group had a greater effect than the guided imagery group. Thus, Yasmin aromatherapy proved to be more effective than guided imagery in improving the sleep quality of the elderly. The effectiveness of Yasmin aromatherapy was influenced by the characteristics of the elderly. Conceptually and practically, Yasmin aromatherapy is a non-pharmacological intervention that is more effective, efficient, and easily accepted by the elderly.